A method for revealing v / i boundaries in monocrystalline silicon using copper nitrate coating and etch thinning
By combining copper nitrate coating with etching and thinning, the problems of cumbersome operation and damage in V/I boundary detection in monocrystalline silicon have been solved. This method achieves efficient and environmentally friendly V/I boundary visualization, simplifies the process and improves detection efficiency.
Patent Information
- Application Number
- CN202611225735.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-11-06
AI Technical Summary
Existing technologies are difficult to efficiently and easily detect and visualize V/I boundaries in single-crystal silicon. Conventional methods are cumbersome to operate, prone to introducing damage, and lack systematic optimization.
A method combining copper nitrate coating and etching thinning is adopted. By coating the surface of single-crystal silicon with copper nitrate solution and performing high-temperature heat treatment, copper atoms diffuse into the defect and precipitate. Subsequently, etching thinning is carried out with a mixed acid solution of a specific ratio, and the V/I boundary is revealed simultaneously.
It simplifies the operation process, improves testing efficiency, reduces the amount of chemical reagents used and pollutant emissions, ensures a clear visibility of the V/I boundary, and significantly improves environmental compliance and safety.
Smart Images

Figure CN123046089A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor material defect detection technology, specifically to a method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate. Background Technology
[0002] With the rapid development of integrated circuit technology, the quality requirements for single-crystal silicon substrates are becoming increasingly stringent. In silicon single crystals grown using the Czochralski method, various types of intrinsic defects inevitably exist within the crystal due to the influence of the crystal pulling rate and the axial temperature gradient near the solid-liquid interface. Among these, the distribution and aggregation of intrinsic point defects—vacancies and interstitial atoms—directly determine the crystal quality. According to the relationship between the V / G ratio and the critical value, when V / G is greater than the critical value, vacancy-type defects dominate the crystal; when V / G is less than the critical value, interstitial defects dominate. The V / I-ring, or V / I boundary, is precisely the radial boundary where the crystal transitions from a vacancy-dominated region to an interstitial atom-dominated region.
[0003] Accurate detection and visualization of V / I boundaries are crucial for evaluating crystal growth processes, optimizing pulling speed parameters, and controlling defect distribution. Currently, commonly used detection methods include oxidation-induced stacking fault testing, native crystal grain testing, annealing combined with X-ray morphology, and micro-defect etching. However, these methods all have limitations in practical applications: oxidation-induced stacking fault and native crystal grain testing typically only reflect the boundaries of specific defect types, making it difficult to comprehensively and directly present the complete morphology of V / I boundaries; annealing combined with X-ray morphology requires sophisticated equipment and involves complex procedures, hindering widespread adoption; and conventional selective etching methods often fail to effectively visualize V / I boundaries, especially when defect sizes are small. Ordinary etching solutions lack sufficient aggression to form clearly identifiable pits, easily leading to blurred boundaries or missed detections, thus severely impacting the accurate determination of the V / I transition zone.
[0004] Copper embellishment technology has gained attention in recent years as a defect display method, particularly for its "magnification" effect on small-sized defects. For example, defects such as native crystal particles, which are only tens of nanometers in size, are almost impossible to directly reveal in conventional preferred etching. Copper embellishment technology, however, involves coating the silicon wafer surface with a copper-containing compound, followed by high-temperature heat treatment to allow copper atoms to diffuse into the silicon substrate. Rapid cooling then causes the copper atoms to form supersaturated precipitates at the defect sites, significantly increasing the defect volume and making it clearly identifiable through subsequent preferred etching. However, existing copper embellishment technologies still suffer from problems such as complex processes, low efficiency, and a lack of systematic optimization in the selection of etching solutions when applied to the precise display of V / I boundaries. Furthermore, conventional silicon wafer defect detection often requires sample thinning for observation, but existing thinning processes are usually separate from defect display processes, which is cumbersome and prone to introducing additional damage. Summary of the Invention
[0005] This invention addresses the shortcomings of existing technologies by providing a method for revealing the V / I boundary in single-crystal silicon using copper nitrate coating and etching thinning. This method removes the interference layer on the single-crystal silicon surface while simultaneously performing selective etching on the copper-defect areas, achieving complete revealing of the V / I boundary in one step.
[0006] The technical solution adopted in this invention is: a method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate, comprising the following steps: S1. Pre-prepared mixed acid solution: A mixed acid solution in a specific ratio is prepared in advance for use in subsequent steps; S2. Sample polishing pretreatment: Cut a single crystal silicon sample block from the single crystal silicon rod, perform single-sided physical grinding and polishing on the sample block, clean the polished single crystal silicon sample block, and then soak the cleaned single crystal silicon sample block in the mixed acid solution prepared in step S1 to perform chemical polishing, so that the surface of the sample block is flat and bright and the thickness reaches the preset value. S3, Copper nitrate solution coating: Copper nitrate solution is coated onto the surface of the single crystal silicon sample block to be tested after step S1, and a copper nitrate film is formed after drying; S4. High-temperature heat treatment: The single-crystal silicon sample coated with copper nitrate film in step S3 is placed in a heat treatment furnace and subjected to constant temperature heat treatment at a preset temperature to allow copper atoms to diffuse into the silicon substrate. Then, it is cooled to room temperature to allow copper atoms to precipitate at the defects. S5. Etching and thinning treatment: The single-crystal silicon sample after step S4 is cleaned and then immersed in the mixed acid solution prepared in step S1 for etching and thinning to a specific thickness. This allows for selective etching of the copper decoration defect area while removing the surface interference layer, thus revealing the V / I boundary. After the single-crystal silicon sample is etched and thinned to a specific thickness, it is taken out and cleaned to obtain a cleaned single-crystal silicon sample with the V / I boundary revealed. S6. Sample observation: Place the single-crystal silicon sample obtained in step S5 under a strong light and observe and record the V / I boundary distribution.
[0007] As a preferred embodiment, in step S1, the mixed acid solution is prepared by mixing HNO3, HF and HAC in a specific volume ratio, and the volume ratio of each component in the solution is HNO3:HF:HAC=10:3:4.
[0008] As a preferred embodiment, in step S2, the initial cutting thickness of the single-crystal silicon sample is 2.2mm-2.3mm.
[0009] Further, in step S2, the physical grinding specifically involves: grinding the single-crystal silicon sample block on one side using an etching thinning machine to reduce the sample block thickness to 2.1 to 2.2 mm; the cleaning operation of the single-crystal silicon sample block specifically involves: rinsing the single-crystal silicon sample block after physical grinding with flowing distilled water for 20 to 40 seconds, cleaning 3 to 5 times, and then drying its surface with nitrogen gas after cleaning; the chemical polishing treatment specifically involves: immersing the ground sample block in a mixed acid solution and polishing it to reduce the sample block thickness to 2.0 mm.
[0010] As a preferred embodiment, in step S3, the copper nitrate solution is prepared as follows: copper nitrate and pure water are weighed according to the mass ratio of Cu(NO3)2:H2O=250g:200g, the two are mixed evenly, and large particles in the solution are filtered out by a 0.45μm filter membrane to obtain the desired copper nitrate solution.
[0011] As a preferred embodiment, in step S3, the coating method is as follows: 2-3 drops of copper nitrate solution are added to the surface of the single-crystal silicon sample to be tested, and the solution is uniformly coated on the entire surface to be tested with lint-free paper. The sample is then dried at 50-60℃ for 30 minutes to form a thin and continuous copper nitrate film.
[0012] As a preferred embodiment, in step S4, the preset temperature is 900℃, and the constant temperature heat treatment time is 6-8 minutes; the heat treatment furnace is a muffle furnace; the specific operation of the constant temperature heat treatment is as follows: several sample blocks with the coating surface facing up are placed upright on a quartz boat, and when the temperature of the muffle furnace reaches 900℃, the quartz boat is placed into the furnace. When the furnace temperature rises back to 900℃, the timing of the constant temperature is started, and the time from when the quartz boat enters the furnace to when the furnace temperature rises back to the preset temperature is controlled within 5 minutes.
[0013] As a preferred embodiment, in step S5, the specific thickness of the etching thinning is: a reduction of 500μm-800μm on the upper surface of the single-crystal silicon sample.
[0014] As a preferred embodiment, in step S5, the specific operation of the etching and thinning is as follows: the single crystal silicon sample obtained in step S4 is immersed in the mixed acid solution prepared in step S1 for etching and thinning until the thickness of the single crystal silicon sample is reduced by 500μm-800μm; the etching and thinning time range is 30-60min.
[0015] As a preferred embodiment, the cleaning step in step S4 is as follows: the etched and thinned single-crystal silicon sample is cleaned with distilled water for 20-40 seconds, repeated 3-5 times, and then the surface is dried with nitrogen.
[0016] The beneficial effects of this invention are: To address the shortcomings of existing technologies, this invention provides a method for revealing the V / I boundary in single-crystal silicon using copper nitrate coating and etching to thin the silicon. Through optimized structural design, this invention achieves the following technical advantages: Firstly, by controlling the corrosion thinning thickness within a specific range of 500μm-800μm, this invention enables a single corrosion thinning process to simultaneously achieve the predetermined removal amount while simultaneously completing the selective corrosion of copper decoration defect areas. This combines the two processes of thinning and defect visualization into one, achieving complete visualization of the V / I boundary in one step. This solves the technical problem in the prior art where the thinning process and defect visualization process are separated, leading to cumbersome operation and easy introduction of additional damage. It greatly simplifies the operation process and improves detection efficiency.
[0017] Secondly, this invention uses a chromium-free mixed acid solution prepared by HNO3, HF, and HAC in a volume ratio of 10:3:4 as the etching solution. The strong oxidizing property of HNO3 provides a high etching rate, and HF reacts with the reaction intermediate SiO2 to form a complex H2SiF6 to promote the continuous reaction. At the same time, the mixed acid solution achieves selective etching by taking advantage of the difference in etching rate of different doping concentrations and electrochemically active regions. It has significant advantages in terms of safety, health, and environmental compliance, and solves the technical problems of existing chromium-containing etching solutions posing great health hazards to operators and causing serious environmental pollution.
[0018] Thirdly, this invention achieves effective decoration with a single coating of copper nitrate solution, significantly reducing the amount of chemical reagents and pollutant emissions compared to existing methods that require multiple coatings. Simultaneously, this etching solution eliminates the use of traditional chromium-containing systems (such as CrO3), thus removing the carcinogen at the source, and simplifies the preparation process, further enhancing operational safety and environmental compliance. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 These are comparative photographs of the V / I-ring morphology of the sample surface after the initial etching and thinning in Examples 1 to 5 of the present invention (where reference numerals a to e correspond to Examples 1 to 5 respectively). Figure 2 Comparative photographs of the V / I-ring morphology of the sample surface after secondary etching and thinning in Examples 3 to 5 of the present invention (where reference numerals c1 to e1 correspond to Examples 3 to 5 respectively). Detailed Implementation
[0021] The present invention will now be described in detail through exemplary embodiments. However, it should be understood that, without further description, elements, structures, and features in one embodiment may be advantageously incorporated into other embodiments.
[0022] It should be noted that, unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by one of ordinary skill in the art to which this invention pertains. The terms "a," "an," or "the," and similar words used in the specification and claims of this patent application do not express a limitation of quantity, but rather indicate the presence of at least one; terms such as "comprising" or "including" indicate that the elements or objects preceding "comprising" encompass the elements or objects listed following "comprising" or "including" and their equivalents, but do not exclude other elements or objects having the same function.
[0023] In the following examples, the monocrystalline silicon raw material is a crystal rod labeled 26M2AT.
[0024] Example 1: The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate as described in this embodiment specifically includes the following steps: S1. Pre-prepared mixed acid solution: Measure nitric acid, hydrofluoric acid and glacial acetic acid according to the volume ratio of HNO3:HF:HAC=10:3:4, mix the three evenly to prepare a mixed acid solution for use in subsequent steps S2 chemical polishing and S5 etching and thinning.
[0025] S2. Sample polishing pretreatment: A single-crystal silicon sample of a certain thickness (about 2.2-2.3 mm) is cut from the single-crystal rod. The single-crystal silicon sample is ground on one side using an etching thinning machine to make the sample surface smooth and bright (thickness 2.1 mm). After physical grinding, the single-crystal silicon sample is rinsed with flowing distilled water for 20 seconds, and cleaned 3 times. After cleaning, the surface is dried with nitrogen. Then, the cleaned sample is immersed in the mixed acid solution prepared in step S1 and chemically polished to further reduce the thickness of the sample to 2.0 mm, with a bright surface free of acid marks and oxidation.
[0026] S3. Copper nitrate solution coating: Weigh copper nitrate and pure water according to the mass ratio of Cu(NO3)2:H2O=250g:200g. After mixing them evenly, filter the solution through a 0.45μm filter membrane to remove large particles and obtain the required copper nitrate solution. Use a dropper to drop 2-3 drops of copper nitrate solution onto the unpolished surface of the single crystal silicon sample. Use lint-free paper to coat the entire unpolished surface of the single crystal silicon sample with the copper nitrate solution. Dry at 60℃ for 30 minutes until the liquid on the sample surface no longer flows, producing a thin and continuous copper nitrate film. This avoids uneven copper nitrate coating on the surface from affecting the final display effect.
[0027] S4. High-temperature heat treatment: Several single-crystal silicon samples coated with copper nitrate film in step S3 are placed upright on a quartz boat with the coated surface facing out. When the temperature of the muffle furnace reaches 900℃, the quartz boat containing the samples is placed into the muffle furnace. Timing starts when the furnace temperature rises back to 900℃. The constant temperature heat treatment lasts for 6 minutes. To avoid the influence of temperature, the time from when the quartz boat enters the furnace to when the furnace temperature rises back to the preset temperature is controlled within 5 minutes. There are no requirements for the atmosphere inside the muffle furnace. After the constant temperature is completed, the quartz boat is taken out and naturally cooled to room temperature, so that copper atoms preferentially precipitate out at defects such as vacancies or interstitial atoms in the silicon substrate, thereby achieving copper decoration of defects.
[0028] S5. Etching and Thinning Treatment: After cooling the single-crystal silicon sample treated in step S4 to room temperature, wash it with distilled water for 20 seconds, repeating 3 times. Then, immerse the single-crystal silicon sample in a mixed acid solution for etching and cleaning for 30-60 minutes (adjust the time flexibly according to the etching rate of the mixed acid). Control the etching and thinning amount to 500 μm (i.e., the thickness of the sample after thinning is 1.5 mm). After the single-crystal silicon sample was etched and thinned to 1.5 mm, it was taken out, washed with distilled water for 20 seconds, and repeated 3 times. Then the surface was dried with nitrogen to obtain a single-crystal silicon sample with a clear V / I boundary.
[0029] S6. Sample observation: Place the single-crystal silicon sample obtained in step S5 under a strong light and observe and record the V / I boundary distribution.
[0030] The reaction mechanism in this embodiment is as follows: This invention selectively embellishes defect sites with copper nitrate, causing weak defects to exhibit observable size magnification during subsequent etching. The defects are amplified after copper nitrate embellishment, and the chromium-free mixed acid solution avoids the use of highly toxic and carcinogenic CrO3, offering significant advantages in safety, health, and environmental compliance. Furthermore, it exhibits selectivity in etching silicon regions with different doping concentrations or electrochemical activities, allowing for simultaneous surface processing and defect display when the sample is etched to a thickness of 500-800 μm.
[0031] The mixed acid solution achieves selective etching by leveraging the differences in etching rates for different doping concentrations and electrochemically active regions, thereby clearly exposing the decorated defects. Furthermore, when the sample thickness is reduced to 500μm–800μm, etching and defect exposure can be completed in one step, combining processing efficiency with detection sensitivity. In this process, the key to the mixed acid etching solution's effectiveness in achieving sample thinning and selective etching lies in its influence on the etching effect on the silicon wafer surface. The strong oxidizing property of HNO3 significantly increases the corrosion rate. The cathodic reaction is: HNO3 + 3H+ - 3e- → NO↑ + 2H2O HF reacts with the intermediate product SiO2 to form the complex H2SiF6, which promotes the reaction. The entire reaction is: Si + HNO3 + 6HF → H2SiF6 + HNO2 + H2↑ + H2O.
[0032] The overall reaction achieves corrosion thinning and defect exposure of the single-crystal silicon sample. HNO3 in the mixed acid solution provides strong oxidizing properties to accelerate corrosion. HF reacts with the reaction intermediate SiO2 to generate the complex H2SiF6 to promote the continuous reaction. Moreover, the mixed acid solution has selective corrosion effect on different doping concentrations and electrochemically active areas, so that while removing the surface interference layer, selective corrosion is carried out on the copper decoration defect area at the same time, making the V / I boundary clearly visible. Example 2: The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate as described in this embodiment specifically includes the following steps: S1. Pre-prepared mixed acid solution: Measure nitric acid, hydrofluoric acid and glacial acetic acid according to the volume ratio of HNO3:HF:HAC=10:3:4, mix the three evenly to prepare a mixed acid solution for use in subsequent steps S2 chemical polishing and S5 etching and thinning.
[0033] S2. Sample polishing pretreatment: A single-crystal silicon sample of a certain thickness (about 2.2-2.3 mm) is cut from the single-crystal rod. The single-crystal silicon sample is ground on one side using an etching thinning machine to make the sample surface smooth and bright (thickness 2.1 mm). After physical grinding, the single-crystal silicon sample is rinsed with flowing distilled water for 40 seconds, and cleaned 5 times. After cleaning, the surface is dried with nitrogen. Then, the cleaned sample is immersed in the mixed acid solution prepared in step S1 and chemically polished to further reduce the thickness of the sample to 2.0 mm, with a bright surface free of acid marks and oxidation.
[0034] S3. Copper nitrate solution coating: Weigh copper nitrate and pure water according to the mass ratio of Cu(NO3)2:H2O=250g:200g. After mixing them evenly, filter the solution through a 0.45μm filter membrane to remove large particles and obtain the required copper nitrate solution. Use a dropper to drop 2-3 drops of copper nitrate solution onto the unpolished surface of the single crystal silicon sample. Use lint-free paper to coat the entire unpolished surface of the single crystal silicon sample with the copper nitrate solution. Dry at 50℃ for 30 minutes until the liquid on the sample surface no longer flows, producing a thin and continuous copper nitrate film. This avoids uneven copper nitrate coating on the surface from affecting the final display effect.
[0035] S4. High-temperature heat treatment: Several single-crystal silicon samples coated with copper nitrate film in step S3 are placed upright on a quartz boat with the coated surface facing out. When the temperature of the muffle furnace reaches 900℃, the quartz boat containing the samples is placed into the muffle furnace. Timing starts when the furnace temperature rises back to 900℃. The constant temperature heat treatment lasts for 6 minutes. To avoid the influence of temperature, the time from when the quartz boat enters the furnace to when the furnace temperature rises back to the preset temperature is controlled within 5 minutes. There are no requirements for the atmosphere inside the muffle furnace. After the constant temperature is completed, the quartz boat is taken out and naturally cooled to room temperature, so that copper atoms preferentially precipitate out at defects such as vacancies or interstitial atoms in the silicon substrate, thereby achieving copper decoration of defects.
[0036] S5. Etching and Thinning Treatment: After cooling the single-crystal silicon sample treated in step S4 to room temperature, rinse it with distilled water for 20 seconds, repeating 3 times. Then, immerse the single-crystal silicon sample in a mixed acid solution for etching and cleaning for 30-60 minutes (adjust the time flexibly according to the etching rate of the mixed acid). Control the etching and thinning amount to 800 μm (i.e., the thickness of the sample after thinning is 1.2 mm). After the single-crystal silicon sample was etched and thinned to 1.5 mm, it was taken out, washed with distilled water for 40 seconds, and repeated 5 times. Then the surface was dried with nitrogen gas to obtain a single-crystal silicon sample with a clear V / I boundary.
[0037] S6. Sample observation: Place the single-crystal silicon sample obtained in step S5 under a strong light and observe and record the V / I boundary distribution.
[0038] Example 3: The difference between this embodiment and Embodiment 1 is that steps S1 to S4 are the same, and the remaining steps are as follows: After cooling the single-crystal silicon sample processed in step S4 to room temperature, wash it with distilled water for 20 seconds, repeating 3 times. Then, immerse the single-crystal silicon sample in a mixed acid solution for 30-60 minutes of etching cleaning (adjust the time flexibly according to the rate of mixed acid etching). Control the etching thinning amount to 400 μm (i.e., the thickness of the sample after thinning is 1.6 mm). After the single-crystal silicon sample was etched and thinned to 1.6 mm, it was taken out, washed with distilled water for 20 seconds, and repeated 3 times. Then the surface was dried with nitrogen to obtain a single-crystal silicon sample with a clear V / I boundary.
[0039] S6. Sample observation: Place the single-crystal silicon sample obtained in step S5 under a strong light and observe and record the V / I boundary distribution.
[0040] S7. Perform secondary etching on the single-crystal silicon sample obtained in step S5 to determine the optimal etching thinning process. Specifically, wash the single-crystal silicon sample after step S5 with distilled water for 20 seconds, repeat 3 times, and then immerse the single-crystal silicon sample in a mixed acid solution for 30-60 minutes of etching cleaning (adjust the time flexibly according to the reaction of the mixed acid etching speed). Control the secondary etching thinning amount to 300um (i.e. the thickness of the sample after thinning is 1.3mm). When the single-crystal silicon sample is etched and thinned to 1.3mm, take it out, wash it with distilled water for 40 seconds, repeat 5 times, and then blow dry the surface with nitrogen to obtain a single-crystal silicon sample with a clear V / I boundary.
[0041] S8. Sample observation: Place the single-crystal silicon sample obtained in step S7 under a strong light and observe and record the V / I boundary distribution.
[0042] Example 4: The difference between this embodiment and embodiment three is that steps S1 to S6 are the same, and the rest are as follows: S7. The single-crystal silicon sample obtained in step S5 is etched again to determine the optimal etching thinning process. Specifically, the single-crystal silicon sample after step S5 is washed with distilled water for 20 seconds, repeated 3 times. Then, the single-crystal silicon sample is immersed in a mixed acid solution for etching and cleaning for 30-60 minutes (the time is flexibly controlled according to the etching speed of the mixed acid). The amount of thinning in the second etching is controlled at 400 μm (that is, the thickness of the sample after thinning is 1.2 mm). When the single-crystal silicon sample is etched and thinned to 1.2 mm, it is taken out, washed with distilled water for 40 seconds, repeated 5 times, and then the surface is dried with nitrogen to obtain a single-crystal silicon sample with a clear V / I boundary.
[0043] S8. Sample observation: Place the single-crystal silicon sample obtained in step S7 under a strong light and observe and record the V / I boundary distribution.
[0044] Example 5: The difference between this embodiment and embodiment three is that steps S1 to S6 are the same, and the rest are as follows: S7. Perform secondary etching on the single-crystal silicon sample obtained in step S5 to determine the optimal etching thinning process. Specifically, wash the single-crystal silicon sample treated in step S5 with distilled water for 20 seconds, repeat 3 times, and then immerse the single-crystal silicon sample in a mixed acid solution for 30-60 minutes of etching cleaning (adjust the time flexibly according to the reaction of the mixed acid etching speed). Control the secondary etching thinning amount to 700um (i.e. the thickness of the sample after thinning is 0.9mm). When the single-crystal silicon sample is etched and thinned to 0.9mm, take it out, wash it with distilled water for 40 seconds, repeat 5 times, and then blow dry the surface with nitrogen to obtain a single-crystal silicon sample with a clear V / I boundary.
[0045] S8. Sample observation: Place the single-crystal silicon sample obtained in step S7 under a strong light and observe and record the V / I boundary distribution.
[0046] The test results for each embodiment are shown in the table below:
[0047] Performance comparison: 1. Divergence in Initial Corrosion Thinning Effect: After the first corrosion thinning, the V / I-ring patterns on the surfaces of the samples from Example 1 (1.5 mm) and Example 2 (1.2 mm) were clear and well-defined, with corrosion pits distributed uniformly in a bright star shape, demonstrating excellent display effects. However, in Examples 3-5, although patterns were visible on the surfaces after the first corrosion thinning (all 1.6 mm), the uniformity of the boundaries was poor, and the depth of the bright star-shaped corrosion pits varied, resulting in only average display effects. These results indicate that when the thickness after thinning is 1.6 mm, it approaches or reaches the upper limit threshold for clear pattern display, and the interfering layer has not been completely removed, limiting the full progress of selective corrosion.
[0048] 2. Verification of the lower limit of thickness by secondary etching: Examples 3-5 were subjected to secondary etching to thin to different thicknesses: The patterns of Examples 3 (1.3 mm) and 4 (1.2 mm) were restored to be clear and uniform, with excellent display effect; Example 5 (0.9 mm) showed blurred patterns and defects and bright spots caused by over-etching, confirming that 0.9 mm was below the lower limit threshold of V / I-ring structural integrity, and the excessive amount of etching removal destroyed the target structure.
[0049] 3. Establishment of Core Variables and Optimal Process Window: By combining copper embellishment with stepwise etching thinning, it was confirmed that the amount of material removed by etching is the most sensitive core variable affecting the V / I-ring development quality. Based on all experimental results, the optimal thickness window is 1.2mm-1.5mm (corresponding to an etching thinning amount of 500μm-800μm). Within this window, the copper embellishment-guided preferential etching and interference layer removal are completed simultaneously in the same thinning process. This completely removes the surface interference layer without damaging the V / I-ring structure due to excessive etching, resulting in the clearest, most stable, and uniformly shaped V / I-ring pattern.
[0050] 4. Thickness Limits: When the thickness after thinning is >1.6mm, the amount of corrosion removal is insufficient, the interference layer is not completely removed, the preferred etching is not fully activated, and the pattern display is limited; when the thickness is <0.9mm, the amount of corrosion removal is too large, the structure suffers destructive corrosion, and the pattern becomes blurred and distorted. Therefore, stable display of V / I-ring requires the amount of corrosion removal to be precisely controlled within an appropriate range that is neither insufficient nor excessive.
[0051] 5. Process Simplification Verification: The above experiments demonstrate that copper embellishments can achieve visual marking of defects, while step-by-step etching and thinning are only used as an exploratory method to determine the optimal thickness window. Based on this window, in actual processes, step-by-step processing is unnecessary. Only the amount of material removed by etching and thinning needs to be controlled within the range of 1.2mm-1.5mm corresponding to the final thickness. This allows for simultaneous removal of the interference layer and selective etching in a single thinning step, achieving a clear and complete display of the V / I-ring pattern in one step. As shown in Examples 1 and 2, using one-step etching and thinning to the target thickness simplifies the process while ensuring clear, uniform, and stable V / I-ring pattern boundaries, confirming the simplicity and reliability of the process.
[0052] It should be noted that although the present invention has been described through the above embodiments, the present invention may have many other embodiments. Without departing from the spirit and scope of the present invention, those skilled in the art can obviously make various corresponding changes and modifications to the present invention, but all such changes and modifications should fall within the scope of protection of the appended claims and their equivalents.
Claims
1. A method for revealing V / I boundaries in single crystal silicon using copper nitrate coating and etch thinning, characterized by, Includes the following steps: S1. Pre-prepared mixed acid solution: A mixed acid solution in a specific ratio is prepared in advance for use in subsequent steps; S2. Sample polishing pretreatment: Cut a single crystal silicon sample block from the single crystal silicon rod, perform single-sided physical grinding and polishing on the sample block, clean the polished single crystal silicon sample block, and then soak the cleaned single crystal silicon sample block in the mixed acid solution prepared in step S1 to perform chemical polishing, so that the surface of the sample block is flat and bright and the thickness reaches the preset value. S3, Copper nitrate solution coating: Copper nitrate solution is coated onto the surface of the single crystal silicon sample block to be tested after step S1, and a copper nitrate film is formed after drying; S4. High-temperature heat treatment: The single-crystal silicon sample coated with copper nitrate film in step S3 is placed in a heat treatment furnace and subjected to constant temperature heat treatment at a preset temperature to allow copper atoms to diffuse into the silicon substrate. Then, it is cooled to room temperature to allow copper atoms to precipitate at the defects. S5. Etching and thinning treatment: The single-crystal silicon sample after step S4 is cleaned and then immersed in the mixed acid solution prepared in step S1 for etching and thinning to a specific thickness. This allows for selective etching of the copper decoration defect area while removing the surface interference layer, thus revealing the V / I boundary. After the single-crystal silicon sample is etched and thinned to a specific thickness, it is taken out and cleaned to obtain a cleaned single-crystal silicon sample with the V / I boundary revealed. S6. Sample observation: Place the single-crystal silicon sample obtained in step S5 under a strong light and observe and record the V / I boundary distribution.
2. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 1, characterized in that, In step S1, the mixed acid solution is prepared by mixing HNO3, HF and HAC in a specific volume ratio, and the volume ratio of each component in the solution is HNO3:HF:HAC=10:3:
4.
3. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 1, characterized in that, In step S2, the initial cutting thickness of the single-crystal silicon sample is 2.2mm-2.3mm.
4. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 1, characterized in that, In step S2, the physical grinding specifically involves: grinding the single-crystal silicon sample on one side using an etching thinning machine to reduce the sample thickness to 2.1 to 2.2 mm; the cleaning operation of the single-crystal silicon sample specifically involves: rinsing the physically ground single-crystal silicon sample with flowing distilled water for 20 to 40 seconds, cleaning 3 to 5 times, and then drying its surface with nitrogen gas after cleaning; the chemical polishing treatment specifically involves: immersing the ground sample in a mixed acid solution and polishing it to reduce the sample thickness to 2.0 mm.
5. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 1, characterized in that, In step S3, the copper nitrate solution is prepared as follows: copper nitrate and pure water are weighed according to the mass ratio of Cu(NO3)2:H2O=250g:200g, the two are mixed evenly, and large particles in the solution are filtered out by a 0.45μm filter membrane to obtain the desired copper nitrate solution.
6. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 5, characterized in that, In step S3, the coating method is as follows: 2-3 drops of copper nitrate solution are added to the surface of the single crystal silicon sample to be tested, and the solution is uniformly coated on the entire surface to be tested with lint-free paper. The sample is then dried at 50-60℃ for 30 minutes to form a thin and continuous copper nitrate film.
7. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 1, characterized in that, In step S4, the preset temperature is 900℃, and the constant temperature heat treatment time is 6-8 minutes; the heat treatment furnace is a muffle furnace; the specific operation of the constant temperature heat treatment is as follows: several sample blocks with the coating surface facing up are placed upright on a quartz boat. When the temperature of the muffle furnace reaches 900℃, the quartz boat is placed into the furnace. When the furnace temperature rises back to 900℃, the timing of the constant temperature is started, and the time from the quartz boat entering the furnace to the furnace temperature rising back to the preset temperature is controlled within 5 minutes.
8. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 1, characterized in that, In step S5, the specific thickness of the etching thinning is: a reduction of 500μm-800μm on the upper surface of the single-crystal silicon sample.
9. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 8, characterized in that, In step S5, the specific operation of the etching and thinning is as follows: the single crystal silicon sample obtained in step S4 is immersed in the mixed acid solution prepared in step S1 for etching and thinning until the thickness of the single crystal silicon sample is reduced by 500μm-800μm; the etching and thinning time range is 30-60min.
10. The method for revealing the V / I boundary in single-crystal silicon by coating and etching with copper nitrate according to claim 1, characterized in that, The cleaning step described in step S4 is as follows: the etched and thinned single-crystal silicon sample is cleaned with distilled water for 20-40 seconds, repeated 3-5 times, and then the surface is dried with nitrogen.
